Pressure-induced shift of effective Ce valence, Fermi energy and phase boundaries in CeOs4Sb12. (1st April 2022) - Götze, K; Pearce, M J; Coak, M J; Goddard, P A; Grockowiak, A D; Coniglio, W A; Tozer, S W; Graf, D E; Maple, M B; Ho, P-C; Brown, M C; Singleton, J
Abstract: CeOs4 Sb12, a member of the skutterudite family, has an unusual semimetallic low-temperature L -phase that inhabits a wedge-like area of the field H —temperature T phase diagram. We have conducted measurements of electrical transport and megahertz conductivity on CeOs4 Sb12 single crystals under pressures of up to 3 GPa and in high magnetic fields of up to 41 T to investigate the influence of pressure on the different H – T phase boundaries. While the high-temperature valence transition between the metallic H -phase and the L -phase is shifted to higher T by pressures of the order of 1 GPa, we observed only a marginal suppression of the S -phase that is found below 1 K for pressures of up to 1.91 GPa. High-field quantum oscillations have been observed for pressures up to 3.0 GPa and the Fermi surface of the high-field side of the H -phase is found to show a surprising decrease in size with increasing pressure, implying a change in electronic structure rather than a mere contraction of lattice parameters. We evaluate the field-dependence of the effective masses for different pressures and also reflect on the sample dependence of some of the properties of CeOs4 Sb12 which appears to be limited to the low-field region.